The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/1744-9987.12142
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Ion Selective Electrode Methods Potentially Overestimate Peritoneal Dialysate Sodium Losses

Abstract: Measurements of dialysate sodium are used to estimate peritoneal dialysis sodium losses and sodium sieving, a measure of hydraulic permeability of the peritoneum. Peritoneal dialysates differ from serum samples in terms of pH, osmolality, protein and glucose concentration. We wished to determine whether these factors affected sodium measurement. Dialysate samples were taken from 52 consecutive peritoneal dialysis patients attending for a standard peritoneal dialysis equilibrium test (PET), 20 with standard lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 15 publications
(19 reference statements)
0
36
0
Order By: Relevance
“…* P < 0.05, ** P < 0.01, *** P < 0.001 vs. Fast transporter. Dialysate to serum creatinine ratio (4 h Dialysate/Serum creatinine) .). N terminal brain natriuretic peptide (NT‐proBNP), extracellular water/total body water ratio (ECW/TBW), skeletal muscle mass (SMM).…”
Section: Resultsmentioning
confidence: 99%
“…* P < 0.05, ** P < 0.01, *** P < 0.001 vs. Fast transporter. Dialysate to serum creatinine ratio (4 h Dialysate/Serum creatinine) .). N terminal brain natriuretic peptide (NT‐proBNP), extracellular water/total body water ratio (ECW/TBW), skeletal muscle mass (SMM).…”
Section: Resultsmentioning
confidence: 99%
“…The higher effect estimate and the higher proportion of hyponatraemia in the younger age group might be partially explained by the higher proportion of patients with diabetic nephropathy in this group (50%) compared to middle (24%) and the older (25%) age groups. There has been debate as to the effect of increasing glucose concentrations on the measurement of serum sodium using indirect potentiometer and flame photometry [14], and potential correction factors for adjusting serum sodium for glucose, with some studies reporting no difference in serum sodium concentration between diabetic and non-diabetic dialysis patients [6,15]. Previous observational studies have suggested greater inter-dialytic weight gains in diabetic patients [16], and greater ratio of extracellular to total body water in diabetic peritoneal dialysis patients [17], suggesting that hyponatraemia in diabetic dialysis patients may have an over hydration component, perhaps due to increased thirst.…”
Section: Discussionmentioning
confidence: 99%
“…This method is linear up to 2.14 g/L (higher concentration samples were diluted to bring them into range). Serum albumin was measured by bromcresol green method (P module analyzer, Roche Integra, Roche Diagnostics ). C‐reactive protein (CRP) was measured using the same assay as the UK National Amlyoid Centre, with values reported down to < 1 mg/L, and hemoglobin by an automated counter (Sysmex XN900, Sysmex Corporation, Kobe, Japan) .…”
Section: Methodsmentioning
confidence: 99%